CoCO3 hierarchical structure embedded on g-C3N4 nanosheets to assemble 3D/2D Z-scheme heterojunction towards efficiently and stably photocatalytic hydrogen production. (13th September 2021) - Dong, Hongjun; Xiao, Mengya; Zhu, Daqiang; Zuo, Yan; Cheng, Shasha; Han, Zhonghui; Li, Chunmei
Abstract: Structure and interface control of heterojunction is usually a challenging issue to improve the photocatalytic performance. Herein, a new 3D/2D CoCO3 /g-C3 N4 heterojunction is assembled by embedding hexahedral CoCO3 on g-C3 N4 nanosheets. The unique step-like hierarchical structure of CoCO3, the formed built-in electric field and Z-scheme charge transfer behavior at the interface jointly drive the high-efficient separation of photogenerated carriers to boost the photocatalytic H2 production. It achieves the optimal H2 production rate that is almost 2.6 times than g-C3 N4, apparent quantum efficiency (AQE) of 10.1% at 400 nm and continuous running of 60 h over the 3D/2D CoCO3 /g-C3 N4 heterojunction. This work endows a fresh structural control strategy for the fabrication of 3D/2D Z-scheme heterojunction to improve the photocatalytic H2 production performance. Highlights: CoCO3 step-like hierarchical structure avails to form built-in electric field. 3D/2D heterojunction is prepared by embedding hexahedral CoCO3 on g-C3 N4 surface. Z-Sheme heterostructure promotes interfacial transfer and separation of carriers. The work has insight into a fresh structural control strategy.